The economic and quality-of-life benefits of Helicobacter pylori eradication in chronic duodenal ulcer disease–a community-based study. Issue 837 (July 1995) - Phull, P. S.; Ryder, S. D.; Halliday, D.; Price, A. B.; Levi, A. J.; Jacyna, M. R.
Abstract : A policy of Helicobacter pylori eradication in patients with duodenal ulceration on long-term acid-suppressing therapy was evaluated in a prospective study amongst a general practice population, with particular reference to economic and quality-of-life benefits. One hundred and sixty-eight patients on long-term acid-suppressing therapy had chronic duodenal ulcer disease of whom 88 were eligible for the study; 45 patients attended for review, with 42 testing positive for H pylori (as assessed by 13C-urea breath test). The median duration of acid-suppressing therapy was six years (maximum 15 years); 47.6% of the patients were using additional antacids and 80.9% still experienced epigastric discomfort. Two-thirds (28/42) of the patients eradicated H pylori. Successful eradication was associated with a highly significant reduction in all symptoms. At 12 months follow-up, heartburn had decreased from 28.7% to 7.1%, epigastric discomfort from 75% to 3.6%, nausea from 32.1% to 0% and wind from 50% to 0%. Of the patients that eradicated H pylori 96.4% reported an improvement in their general health compared to none of those that remained H pylori positive. Successful H pylori eradication therapy scored higher on satisfaction ratings than long-term acid-suppressing therapy. Eradication of H pylori resulted in 27/28 patients being able to discontinue acid-suppressing therapy, representing a 5.8% reduction in the use of such drugs per year in the local general practice population. A policy of H pylori eradication in chronic duodenal ulcer disease reduces the use of long-term acid-suppression therapy in general practice. This has important financial implications as well as offering considerable symptomatic benefits to the patients and improving their quality of life.